1996
DOI: 10.1007/bf02630737
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to Cr(VI): comparison between chromium levels in lymphocytes, erythrocytes, and urine

Abstract: The relationships between chromium (Cr) levels in lymphocytes, erythrocytes, urine, and ambient air were compared among 14 chrome-platers from a metallurgic plant in Bulgaria and two groups of local controls, one from the same heavily polluted industrial town as the chrome-platers (n = 11) and one from a seaside resort town 100 km away (n = 6). Among the chrome-platers, the Cr concentration in peripheral lymphocytes was positively correlated with total Cr and Cr(VI) levels in ambient air and with Cr excretion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 15 publications
2
10
2
Order By: Relevance
“…In our study, the mean RBC-Cr concentration in workers exposed to chromate was 12.45 μg/l, which was lower than the values reported by Costa and by Lukanova in chrome-plate workers 5 38. In contrast, the U-Cr concentration in our investigated subjects was higher than found in previous reports 1–3.…”
Section: Discussioncontrasting
confidence: 89%
“…In our study, the mean RBC-Cr concentration in workers exposed to chromate was 12.45 μg/l, which was lower than the values reported by Costa and by Lukanova in chrome-plate workers 5 38. In contrast, the U-Cr concentration in our investigated subjects was higher than found in previous reports 1–3.…”
Section: Discussioncontrasting
confidence: 89%
“…For confounding factors, it is likely that smoking does not contribute greatly to Cr bioavailability in occupationally exposed individuals, where the exposure originates predominantly from the work process than the contribution of non-occupational sources of exposure, which appears negligible as compared to occupational exposure (Lumens 1993;Lukanova 1996). Apostoli (1997) found that alcohol consumption, smoking habits, residence, and age had no eVect on the U-Cr levels.…”
Section: Discussionmentioning
confidence: 94%
“…Some Weld studies (Lindberg and Vesterberg 1983;Lumens et al 1993;Lukanova et al 1996;Chen et al 2002;Caglieri et al 2006) had been conducted in the plating industry in order to study the relationships between exposure and biological indicators. But the occupational physician has no validated biological exposure indicator for ensuring medical surveillance of exposed workers (Paustenbach et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Cr(VI) is rapidly reduced to Cr(III) via unstable intermediates [Cr(V) and Cr(IV)] inside the RBC. The reduced product binds to hemoglobin and other intracellular proteins, resulting in the elevation of total Cr levels in the RBC fraction of blood for several weeks [51]. Due to its propensity to generate radical species, erythrocytes may be considered as sensitive and intermediate cells in oxidative reactions [64].…”
Section: Introductionmentioning
confidence: 99%